Ethnopedagogy in Primary Schools: Ethnographic Study in Thematic Learning at Ma'arif Setono Jenangan Ponorogo (Journal of Basic Education Research, 2022)
Purpose of the study: This research aims to elucidate the implementation of ethnopedagogy in thematic learning at MI Ma'arif Setono Jenangan Ponorogo and to analyze its impact on students' learning outcomes. Methodology: Utilizing a qualitative research approach with an ethnographic design, this study employed interview, observation, and documentation techniques for data collection. The data were analyzed through domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. Main Findings: The implementation of ethnopedagogy in thematic learning at MI Ma'arif Setono Jenangan involves adapting each theme and material, sourcing from books, and integrating local wisdom content into teaching and learning activities. This encompasses various aspects of local wisdom, including values, norms, beliefs, arts and culture, as well as natural products and resources. The application of ethnopedagogy has positively impacted students' thematic learning outcomes, with students from grades 1 to 6 achieving complete scores on average. Additionally, the implementation of ethnopedagogy has fostered positive changes in students' attitudes, enhancing their character development, fostering a stronger sense of nationalism, and encouraging the preservation of local culture. Novelty/Originality of this study: This research significantly contributes to the advancement of educational practices in Indonesia, particularly at MI Ma'arif Setono Jenangan Ponorogo. Beyond offering insights into the implementation of ethnopedagogy at this specific institution, the study provides valuable perspectives that can be applied and further developed within the broader educational landscape in Indonesia.